PENGARUH LITERASI EKONOMI ISLAM TERHADAP PERILAKU KONSUMTIF (STUDI PADA MAHASISWA PENGGUNA SHOPEEPAY) DI SURABAYA - Lestari, Anisa Dea; Fikriyah, Khusnul (Jurnal Ekonomika dan Bisnis Islam, 2023)
In consumptive behavior which greatly affects economic stability where later the greater the level of consumption, the greater the change in economic activity. For this reason, in student studies it is necessary to pay attention to consumption in Islamic teachings, where economic literacy has no influence on consumptive attitudes. So that someone is lightly interested in a product according to his interest in buying without considering the consequences or needs that are the priority of consumer actions. The purpose of this study is to determine the level of economic literacy in order to open up understanding and knowledge about economic descriptions so that they are free from consumptive attitudes. The type of research used is quantitative. The data source used by the researcher is a primary data source that comes directly from the research subject online via the Google form, so that later the results of the Google form data obtained are measured with a Likert scale. The population in this study are Islamic Economics, Islamic Banking, and Islamic Accounting Students who are Muslim and use the Shopeepay application. Based on the results of this study, variable X (Islamic economic literacy) has no effect on variable Y (consumptive behavior). , and vice versa, if Islamic Economics literacy is low, the consumptive attitude will be even greater.